MICROEPIDEMIOLOGICAL INVESTIGATION OF STRONGYLOIDES STERCORALIS IN INFECTED PATIENTS HOUSES WITH THE HUMAN IMMUNODEFICIENCY VIRUS (HIV) - Cecchetto, Fatima Helena (2007)
A possible association between intestinal parasite infection in immunocompromised patients with and the contamination their domiciliary environment may exist. Therefore, this correlation was studied through a study microepidemiologic by determining the presence of helminths and intestinal coccidian in samples obtaneid from the floor, water and vegetables of common and constant use in houses of patients with the Human Immunodeficiency Virus (HIV+, CD4 lymphocytes ≥ 200 mL, viral load ≈ 10 thousand). The samples were selected by random and systematized sampling. For the analysis of the floor the techniques of Cadwell-Cadwell, Hoffmann, Pons & Janer (HPJ) and modified Kinyoun (hot) were used whereas HPJ, Faust, and the filtration technique with propilethylene filter were used for water and vegetables samples. We found rhabditiform larves of Strongyloides stercoralis in Allium fistolosum (Chinese onion) cultivated in the vegetable garden of one of the 11 patient’s. Although this parasitic form is a non-infective stage for the human, it makes part of the biological cycle of S. stercoralis and it is fundamental for its multiplication and maintenance in the environment. This finding denotes the human ecological importance in the dynamics of the transmission of geohelminths, and alerts to necessity of instructing the population on measured prophylaxes and hygiene, especially to immunocompromised patients.